The Implementation of Restorative Justice in Cases Involving Corporate Perpetrators - Farman, Eka; Suherman, Suherman; Farid , Muhammad; Maskur, Maskur; Syamsuddin, Syamsuddin; Musmuliyadin, Musmuliyadin (International Journal of Law, Crime and Justice, 2025)
This normative legal study examines the potential and challenges of implementing restorative justice approaches in cases involving corporate perpetrators within Indonesia's criminal justice system. The research employs statute, conceptual, and case approaches to analyze legal principles, norms, and court decisions related to corporate criminal liability and restorative justice mechanisms. Through comprehensive literature review of international academic databases and examination of Indonesia's legal framework, including the New Criminal Code of 2023 and Prosecutor's Regulation No. 15 of 2020, the study reveals that restorative justice offers a transformative alternative to traditional retributive models by prioritizing restoration, rehabilitation, and reconciliation between corporate offenders, victims, and affected communities. The dual track system selective model emerges as the most appropriate framework for corporate restorative justice implementation, enabling selective application while maintaining prosecutorial discretion for serious offenses. However, significant challenges persist, including the absence of specific regulatory frameworks for corporate actors, structural complexities arising from the non-personified nature of corporate entities, and profound power imbalances between corporations and victims that threaten process integrity. The study demonstrates that successful implementation requires comprehensive legal reforms, enhanced institutional capacity, robust victim support mechanisms, and safeguards against corporate manipulation. The research concludes that while restorative justice holds considerable promise for enhancing corporate accountability and victim restoration, effective implementation is contingent upon establishing clear legal frameworks, technical guidelines, and protective measures that address inherent power asymmetries between corporate offenders and their victims.